Dissection of signaling pathways regulating TrkB-dependent gephyrin clustering - Wüstner, Lisa-Sophie; Beuter, Simone; Kriebel, Martin; Volkmer, Hansjürgen (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe TrkB receptor is known for its role in regulating excitatory neuronal plasticity. However, accumulating evidence over the past decade has highlighted the involvement of TrkB in regulating inhibitory synapse stability and plasticity, particularly through regulation of the inhibitory scaffold protein gephyrin, although with contradicting results.MethodsIn this study, we extended on these findings by overexpressing rat TrkB mutants deficient in either Shc-or PLCγ-dependent signaling, as well as a kinase-dead mutant, to dissect the contributions of specific TrkB-dependent signaling pathways to gephyrin clustering.ResultsOur results demonstrate that TrkB signaling is required for gephyrin clustering on the perisomatic area of granule cells in the dentate gyrus in vivo. To further investigate, we expressed TrkB wild-type and mutants in hippocampal neurons in vitro.DiscussionUnder basal conditions, TrkB-Shc signaling was important for the reduction of gephyrin cluster size, while TrkB-PLCγ signaling accounts for gephyrin clustering specifically at synaptic sites. Concomitant, impaired PLCγ signaling was associated with disinhibition of transduced neurons. Moreover, chemically induced inhibitory long-term potentiation (chem iLTP) depended on TrkB signaling and the activation of both Shc and PLCγ pathways.ConclusionOur findings suggest a complex, pathway-specific regulation of TrkB-dependent gephyrin clustering, both under basal conditions and during chem iLTP.